TOPOLOGICAL STRUCTURAL STABILITY ON PROJECTED SPACES - Figueroa, Rodiak (2016)
In this work we study the topological structural stability for a family of nonlinear semigroups Th(·) on Banach spaces Xh which dependent on a parameter h.